Infection-provoked Reversible Posterior Leukoencephalopathy Syndrome in Children Experiencing Nephrotic Syndrome: A Case Report - Emami, Elham; Karimi, Ghazaleh; Oroojeni, Atrin (Journal of Pediatric Nephrology, 2025)
Background and Aim: Reversible posterior leukoencephalopathy syndrome (RPLS), also known as posterior reversible encephalopathy syndrome (PRES), is an uncommon and varied cliniconeuroradiological condition that can manifest with a range of clinical symptoms, such as visual disturbances, altered consciousness, headaches, and seizures. Hypertension and immunosuppression are two primary factors that increase the likelihood of developing RPLS. Nevertheless, RPLS can also occur in the presence of other risk factors. Case Presentation: A 10-year-old Asian boy diagnosed with nephrotic syndrome exhibited symptoms of seizures and fever. His blood pressure (BP) was within the normal range, and he received treatment with immunosuppressive medications. Conclusion: In cases where patients with nephrotic syndrome develop an infection, it is important to assess for symptoms of RPLS. Timely diagnosis and proper management of RPLS can help prevent mortality and morbidity.